PELAYANAN LANGSUNG JADI KABUPATEN JOMBANG - Zulfani, Melia Aninda (Faculty of Social and Political Science Universitas Brawijaya, 2017)
Governance today is no longer solely the responsibility of government, but of all the actors in a country. Why this is so, the role of government is certainly still needs related to the provision of public services. The problems that exist in Jombang is difficult licensing services, too complicated, time-consuming, expensive cost plus the community was thinking radically. They still do not understand the meaning of taking care of a license for what and what's in it for them, especially people in remote villages that are unreachable information. Given this reality, Jombang Jombang Regent, H. Suyanto, initiates in licensing by making services with procedure